Sex differences in atrial electrical properties. (19th May 2022) - Giammarino, L; Hof, T; Nimani, S; Alerni, N; Matas, L; Odening, KE
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss Heart Foundation Background: Pronounced sex differences are known in the incidence and recurrence rates of atrial fibrillation (AF). In general, men carry a higher risk for AF - particularly at younger age - during which women are protected. Purpose: In this project, we aimed to investigate electrophysiological properties of the atria that may underlie sex differences in AF development in the younger population. Methods: First, we assessed sex differences in P-wave morphology (duration: PWD; area: PWA, amplitude) in 12-lead ECG in healthy volunteers (men 31.3±1.6 y, n=10; women 29.8±1.6 y, n=10) and wildtype (WT) rabbits (3-6 months, males n=12, females n=15). We investigated sex differences in atrial action potential (AP) in WT rabbits of both sexes using sharp electrode recording technique (males n=5, females n=6). To elucidate underlying mechanisms, sex differences on atrial inwardly rectifying potassium current IK1 at 37°C were evaluated using whole-cell patch-clamp technique in isolated atrial rabbit cardiomyocytes; to evaluate the long-term effect of sex hormones on IK1, we incubated the isolated cardiomyocytes for 24h with 3 or 10µM of 17β-estradiol (EST) or of dihydrotestosterone (DHT). Results: Analyzing ECG parameters (figure 1), we observed a prolonged PWD and an increased PWA both in healthy men (p<0.0001) and in male rabbits (p<0.0001) as compared to healthy women or female rabbits, which may theoretically be due to a slower conduction velocity or longer AP duration in males. Intracellular AP recordings (figure 2A) showed a more negative atrial resting membrane potential (RMP, males -83.07±0.3mV vs. females -74.33±2.6mV, p<0.05) and a prolonged atrial AP duration (APD10, 18.20±3.6ms vs. 10.06±1.9ms, p=0.06; APD50, 36.60±6.6ms vs. 20.06±1.9ms, p<0.05; APD90, 91.00±10.3ms vs. 74.00±4.0ms, p=0.13) in males as compared to females. As highlighted in figure 2B, male atrial cardiomoycytes had smaller IK1 current densities, which could be due to high DHT concentration; in line with these findings (figure 2C) 24h DHT incubation of atrial cardiomyocytes from females reduced IK1, mimicking the sex differences observed. Conclusions: Sex impacts on atrial electrophysiology, resulting in sex differences in P-wave morphology, AP parameters and ionic current densities. Delayed (early) repolarization in males may be causatively linked to the observed changes in P-wave morphology. The reduction of IK1 observed in males may be due to testosterone, since this reduction was observed even in female cardiomyocytes when incubated with DHT.